2016
DOI: 10.1007/s10995-016-1944-x
|View full text |Cite
|
Sign up to set email alerts
|

Are Parental Perceptions of Child Activity Levels and Overall Health More Important than Perceptions of Weight?

Abstract: Objectives To examine relationships between parental perceptions of child weight and overall health, reported lifestyle behaviors and measured body mass index (BMI). Methods Using community-partnered methods, we surveyed families residing in a two census tract area identified for targeted interventions to decrease diabetes related disparities. The survey included demographics, child dietary and physical activity behaviors, and parental perception of child’s health and weight. We measured child BMI using a st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…In NZ, Māori caregivers of children aged 5 years and younger believed that once children started school, they would burn off any excess fat through increased physical activity (27). However, elsewhere, parents of 7-year-old children were more accurate in recognizing their child's overweight or obesity when they perceived their health as poor (29). Indeed, parental recognition of overweight or obesity is more accurate in older than younger children (7,(9)(10)(11).…”
Section: Discussionmentioning
confidence: 99%
“…In NZ, Māori caregivers of children aged 5 years and younger believed that once children started school, they would burn off any excess fat through increased physical activity (27). However, elsewhere, parents of 7-year-old children were more accurate in recognizing their child's overweight or obesity when they perceived their health as poor (29). Indeed, parental recognition of overweight or obesity is more accurate in older than younger children (7,(9)(10)(11).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding healthy eating behavior and parental perceptions, it was revealed that children whose parents misperceived their weight status did not follow the optimal dietary pattern [ 29 ] and that when parents underestimated their child’s weight, those children usually watch television during their meals [ 29 ] and spend fewer hours a day walking [ 28 ]. On the other hand, children whose parents accurately classify their children’s body weight have more healthy habits, e.g., daily breakfast, more exercise, less soft drink consumption and less screen time [ 19 ], and generally their parents try encouraging methods to ameliorate their children’s physical activity level [ 24 ] and eating habits [ 10 ].…”
Section: Study’s Findingsmentioning
confidence: 99%
“…Other studies showed that parents perceived that low physical activity and additional hours of watching television as risk factors of childhood obesity 40 . Furthermore, another study showed that some parents perceived walking and/or running are protective factors against childhood obesity 26 . Finally, one study reported parents' perception regarding to health concerns of childhood obesity, thus parents of obese children are more likely to perceived the risk of hypertension (OR = 1.9), heart disease (OR = 2.26), type 2 diabetes (OR = 2.2) and depression (OR= 1.8) relative to parents of healthy weight children 16 .…”
Section: Parents' Perception Regarding Risk Factors and Health Concermentioning
confidence: 99%